Production of Natural Food Colourants Using Food Grade Microbial Pigments: A New Focus in Industrial Microbiology - Solehin, Siti Najihah; Kamarudin, Kamarul Rahim; Badrulhisham, Nur Sabrina; Mohamed Rehan, ‘Aisyah (Journal of Sustainable Natural Resources, 2020)
In today’s food industry, the new focus on large-scale microbial production of natural food colourants has emerged among the manufacturers due to the relatively costly production of plant-derived food colourants, and the doubtful safety status of inorganic and synthetic colourants. However, it is still very challenging to change the consumers’ reliance on synthetic colourants. In fact, the first European success on the launch of β-carotene from Blakeslea trispora in 1995 has headed more search for new sources of natural food grade microbial pigments. The acceptance and rejection of a microbial food grade pigment by a community of consumers depend on two main contributing factors i.e. the regional and the traditional-based legislations. This paper discusses the classification of natural pigments, the legislation on natural food colourants, the success and new sources of potential pigment-producing microbes, and the advantages of microbial fermentation.